Human epileptic seizure prediction using deep convolutional neural network - Arenas, Angelo V.; Cosme, Jefferson G.
Epilepsy is one of the most common neurological disorders characterized by recurrent and intermittent seizures Researchers have long studied how to detect and predict these seizures and machine learning techniques proved to be the most effective.